2008
DOI: 10.1021/bi800030g
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Primary Radical Pair in Reaction Centers of Heliobacillus mobilis by 13C Photo-CIDNP MAS NMR

Abstract: Photochemically induced dynamic nuclear polarization (photo-CIDNP) has been observed in membrane fragments of heliobacterium Heliobacillus mobilis without further isolation by (13)C magic-angle spinning (MAS) solid-state NMR under continuous illumination with white light. In the (13)C photo-CIDNP MAS NMR spectra of heliobacterial membrane fragments, two sets of signals are observed, allowing characterization of the primary radical pair. One set, showing enhanced absorptive (positive) signals, arises from the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 42 publications
0
53
0
Order By: Relevance
“…Donors have been found to be monomers, asymmetric dimers and symmetric dimers [56]. Also the involvement of the protein matrix in the donor structure has been proposed [12,15]. Two parallel branches have been proposed on the acceptor site [57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Donors have been found to be monomers, asymmetric dimers and symmetric dimers [56]. Also the involvement of the protein matrix in the donor structure has been proposed [12,15]. Two parallel branches have been proposed on the acceptor site [57].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that high-quality photo-CIDNP data can be obtained from membrane-bound RCs [12] and even cells [9]. Hence, even if an RC isolation is not feasible, photo-CIDNP MAS NMR still can be applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCC 6803 [17] -a cyanobacterium -and the firmicute Heliobacillus mobilis. [18] Additionally, there are two more bacterial phyla which contain phototrophic members: chloroflexi and acidobacteria. [19] From both phyla, no experiments with photo-CIDNP MAS NMR have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…frozen natural photosynthetic systems, where it allows for detailed functional analysis 4,5,6,3,7 , as well as a blue-light photoreceptor LOV1-C57S 8,9 . Since all natural photosynthetic systems tested have shown the effect, it has been proposed that the solid-state photo-CIDNP effect is related to the unsurpassed efficiency of natural photosynthetic electron transfer 10 .…”
Section: Introductionmentioning
confidence: 99%